Tinjauan Kimia Medisinal: Hubungan Struktur-Aktivitas Senyawa Bahan Alam sebagai Kandidat Antikanker Payudara - Saeful Amin; Icha Aisah Azzahra; Natasya Zakiatul Awalia Irhan; Syifa Alifia Azzahra (Pusat riset dan Inovasi Nasional, 2026)
Breast cancer remains a major global health challenge, with treatment effectiveness often limited by drug resistance and the toxic side effects of chemotherapy on normal cells. The exploration of bioactive compounds from natural sources through a medicinal chemistry approach offers a promising alternative strategy. This study aims to examine the molecular mechanisms of action and Structure-Activity Relationships (SAR) of various natural compound scaffolds as potential breast anticancer agents. The method employed was a systematic narrative literature review of 15 recent scientific articles evaluating computational parameters, including molecular docking, as well as in vitro and in vivo activities. The results indicate that polyphenols, flavonoids such as quercetin and EGCG, and curcumin possess strong cytotoxic activity and high binding affinity toward cancer-related target macromolecules. SAR analysis demonstrates that key structural features, including the number and position of free phenolic hydroxyl groups, the presence of gallate ester groups, and conjugated diketone systems, play a crucial role in determining ligand receptor complex stability. These interactions are supported by hydrogen bonding, hydrophobic interactions, and favorable steric compatibility within receptor binding sites. Computational findings further suggest that structural optimization can enhance ligand selectivity and improve pharmacokinetic properties. This study concludes that natural phytochemical scaffolds have significant potential as lead compounds and provide a rational basis for Computer-Aided Drug Design in developing more potent, selective, multi-target, and safer breast anticancer therapies.